A Human Capital Theory of Growth: New Evidence for an Old Idea (2014)
In 1960 Theodore Schultz expounded a human capital theory of economic growth that includes three elements: 1) Countries without much human capital cannot manage physical capital effectively, 2) Economic growth can only proceed if physical capital and human capital rise together, and 3) Human capital is the factor most likely to limit growth. I specify Schultz’s theory mathematically and test it in periods when global financial capital was highly mobile. I find that in 1870, 1910, and 2000, the average schooling attainment of the adult population largely determined the stock of physical capital/capita and GDP/capita in 42 market economies.